PENGARUH PIJAT LAKTASI TERHADAP PENGELUARAN KOLOSTRUM PADA IBU POST PARTUM DI WILAYAH KERJA PUSKESMAS SELATBARU - Silvia, Astriana; Sari Tanberika, Fajar; Mardiya, Rizka; Yanti, Rifa (Ensiklopedia of Journal, 2025)
Colostrum is the first milk that comes out, which is often yellow or clear and contains living cells that resemble "white blood cells" which can kill germs and thus protect the baby's body from various infectious diseases. The theory holds that things that stimulate the release of colostrum, one of which is doing lactation massage. Lactation massage is massage along both sides of the spine. The aim of this research is to determine the effect of lactation massage on colostrum production in post partum mothers in the Working Area of the Selatbaru Public Health Center, Bengkalis Regency, Bengkalis Regency in 2024. The type of research used in this research is quantitative research with a Quasi Experimental research design with a post only design with control group approach. The population in this study was post partum mothers in the Selatbaru Health Center Working Area, totaling 32 respondents with a sample of 32 respondents, who were divided into 2 groups, namely 16 intervention groups and 16 control groups using a purposive random sampling technique. This research was carried out in the Selatbaru Community Health Center Work Area in December – February 2025. Data was collected using questionnaires, univariate and bivariate data analysis (t-test). The results of the univariate study, the average colostrum expenditure among postpartum mothers before giving it to the intervention group was 2.25 and after the intervention was 15.88, while the average colostrum expenditure among postpartum mothers before the control group was 1.94 and after the control group was 6.88. There is an effect of lactation massage on colostrum production in postpartum mothers in the Selatbaru Health Center Working Area in 2024 (p-value = 0.000). Advice for mothers who are breastfeeding to do lactation massage so that breast milk production increases.Keywords: Lactation Massage, colostrum production, and Post Partum mothers